2019
DOI: 10.1007/s10681-019-2406-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of donors for low-nitrogen stress with maize lethal necrosis (MLN) tolerance for maize breeding in sub-Saharan Africa

Abstract: After drought, a major challenge to smallholder farmers in sub-Saharan Africa is low-fertility soils with poor nitrogen (N)-supplying capacity. Many challenges in this region need to be overcome to create a viable fertilizer market. An intermediate solution is the development of maize varieties with an enhanced ability to take up or utilize N in severely depleted soils, and to more efficiently use the small amounts of N that farmers can supply to their crops. Over 400 elite inbred lines from seven maize breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…More accurate selection through increased repeatability increases selection response for the trait of interest. Recent combined analysis of the southern Africa regional trials of CIMMYT and partners and managed drought and low‐N stress trials in ESA showed that the repeatability ( H ) of the managed stress trials in this study was lower than that of nonstress trials and that plot residual variance under abiotic stress was high (Weber et al, 2012; Cairns et al, 2013b; Das et al, 2016). In this study, the combined H was above 0.5 for all stress treatments; however, several trials had to be removed due to low H .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…More accurate selection through increased repeatability increases selection response for the trait of interest. Recent combined analysis of the southern Africa regional trials of CIMMYT and partners and managed drought and low‐N stress trials in ESA showed that the repeatability ( H ) of the managed stress trials in this study was lower than that of nonstress trials and that plot residual variance under abiotic stress was high (Weber et al, 2012; Cairns et al, 2013b; Das et al, 2016). In this study, the combined H was above 0.5 for all stress treatments; however, several trials had to be removed due to low H .…”
Section: Discussionmentioning
confidence: 68%
“…Prior to 2009, the lowest phenotyping capacity in the CIMMYT ESA breeding pipeline was for low‐N stress, with less than 10 ha of N‐depleted land available for screening in ESA (Magorokosho et al, 2010). The low‐N phenotyping capacity has recently been expanded, with sites in 10 countries on 48 ha of N‐depleted land (Das et al, 2016). Drought phenotyping capacity has increased since 2006, with managed drought screening capacity increasing from 6 to 35 ha (Magorokosho et al, 2010; Makumbi, 2011; Cairns et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true for tropical maize in which little additional gain in maximum drought-tolerance has been achieved in the last decade [29]. Addressing this issue and hence, ensuring progress in genetic improvement of maize under abiotic stress conditions requires identification of donor lines with beneficial traits that will bring new genetic variation [29,44]. Landrace gene pools of maize from areas that frequently experience DS at elevated temperatures may provide a useful source of novel alleles for abiotic stress tolerance [27,45].…”
Section: Discussionmentioning
confidence: 99%